FORMULASI MINYAK ATSIRI (ESSENTIAL OIL) CENGKEH (OLEUM SYZYGIUM AROMATICUM) PADA PEMBUATAN EAU DE PARFUME - Syafika Itamar; Tanto Pratondo Utomo; Esa Ghanim Fadhallah; Harun Al Raysid (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Eau de parfume (EDP) is a type of perfume or fragrance that has an aromatic concentration of about 15-20% in mL per bottle. Indonesia has the potential of spice plants producing essential oils that can be used as aromatic ingredients for making perfumes, one of which is the clove plant. This study aims to analyze the characteristics of parfum and analyze the cost of production in the best perfume formulation. The study was prepared with a two-factor Complete Randomized Design (RAL) (A-B) with 5 repeats. The treatment in this study is the ratio of clove oil: cocoa scented oil: pine oil: lemongrass oil: coconut scented oil, amounting to (mL) 1:4:1:1:3 (A1B1), 1:4:0,5:0,5:4 (A1B2), 0,8:4:1,1:1,1:1:3 (A2B1), 0,8:4:0,6:0,6:6:4 (A2B2). The parameters observed are hedonic tests of color, aroma, aroma intensity and aroma level as well as the best treatment, namely stain tests, fragrance resistance tests, perfume suitability, and cost of goods produced analysis. The data obtained were analyzed for homogeneity with the Bartlet test, then analyzed for fingerprints (ANARA), and further tests with DMRT. The results showed that the best formulation of Eau de parfume cloves was obtained in the formulation A2B2 ( 4mL coconut : 0.8mL cloves : 4mL cocoa / chocolate : 0.6mL pine : 0.6mL lemongrass). This formulation has specific no stains, with fragrance resistance tests up to 55.57% in the 5th hour, and the suitability of the perfume received by the panelists with a warmwoody scent. The results of the product cost analysis resulted in a selling price of Rp. 50.000 per size of 30 mL.